Analisa dAN Perancangan Sistem Informasi Point of Sales untuk UMKM Studi Kasus: Arjuna Farm - Jefri Junifer Pangaribuan; Okky Putra Barus; Yudhistira Adhitya Pratama; Faisal Nadjar; Ade Maulana (UNIVERSITAS PELITA HARAPAN, 2022)
The Covid-19 pandemic has had an impact on various economic sectors and resulted in a decline in various sectors. In the midst of economic uncertainty due to the COVID-19 pandemic, the Small and Medium Enterprises (SMEs) sector is expected to be the foundation of the national economy that can contribute to the revival of the economy of Indonesia. One of the SMEs that will be supported in this research program is Arjuna Farm and its partners spread across Indonesia. Arjuna Farm has a focus on the livestock sector and also the distribution of various derivative products. One of the obstacles faced by Arjuna Farm partners is in terms of recording the company's operational transactions. The result is the farmers being unable to make the right decisions in managing the business and also developing the business. Therefore, this Community Service will produce a point of sales solution that is suitable for the needs of farmers. In addition, mentoring will be carried out for 1 semesters to ensure that the resulting solutions can be measured for success and also provide optimal benefits for farmers. Keywords: Point of Sales, Farmer, SMEs Bahasa Indonesia Abstrak: Pandemi Covid19 telah memberikan dampak bagi berbagai sector ekonomi dan menghasilkan penurunan di berbagai sector. Di tengah ketidakpastian ekonomi akibat pandemi covid-19, sektor Usaha Kecil dan Menengah (UMKM) diharapkan menjadi pondasi perekonomian nasional yang dapat memberikan kontribusi kepada kebangkitan ekonomi Indonesia. Salah satu UMKM yang akan didukung dalam penelitian ini adalah UMKM Arjuna Farm dan mitra-mitranya yang tersebar di Indonesia. Arjuna Farm memiliki focus pada bidang peternakan dan juga distribusi berbagai produk turunannya. Salah satu kendala yang dialai oleh mitra-mitra Arjuna Farm yaitu dalam hal pencatatan transaksi operasional perusahaan. Yang mana berakibat kepada para peternak tersebut tidak dapat membuat keputusan yang tepat dalam mengelola usaha dan juga mengembangkan usaha. Oleh karena itu PKM ini akan menghasilkan sebuah solusi point of sales yang sesuai untuk kebutuhan para peternak. Selain itu akan dilaksanakan pendampingan selama 1 semester untuk memastikan agar solusi yang dihasilkan dapat diukur keberhasilannya dan juga memberikan benefit yang optimal untuk para peternak. Kata Kunci: Point of Sales, Peternak, UMKM